Cutaneous Melanoma with Tonsillar Metastasis: Treatment with Cryoablation - Dulskas, Audrius; Trakymas, Mantas; Gibavičienė, Jolita; Čepulis, Vytautas; Čižauskaitė, Agnė; Samalavičius, Narimantas (Acta medica Lituanica, 2022)
Metastasis of cutaneous melanoma to the oral cavity is a rare condition. Male patient with cutaneous melanoma metastasis to right tonsil 2 years after radical skin lesion resection was treated with surgery: tonsillectomy and later resection of soft palate were performed. Two years later the patient was diagnosed with progressive disease to right tonsil and soft palate. Rapid inoperable relapse was detected six months later. The patient underwent two procedures of palliative cryoablation of the metastasis. Postoperative course was uneventful. Patient died 7 months later due to progression of the disease. Cryoablation alone or together with surgery may be a relatively safe option for treatment of inoperable disease of head and neck tumours.